Data transfers through the Metaverse in the light of the latest agreements (EU-US). The “parent trap” phenomenon - Cruz Ángeles, Jonatán (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This article conducts a comprehensive analysis of extra-EU data transfers, vital for the implementation and management of the Metaverse, with a particular focus on the regulations of the European Union and the United States. It focuses on the impact of the most crucial legal decisions of the European Court of Justice regarding the protection of European citizens’ personal data in these emerging virtual spaces. It involves a detailed study of specialized doctrine to determine whether the recently unveiled Agreement between the EU and the U.S. on July 10, 2023 is sufficiently robust or whether, failing that, other alternatives or measures need to be investigated that should be considered by technology giants such as Meta. The ultimate goal is to elucidate the real and effective extent of privacy rights and transatlantic safeguarding of personal data in the contemporary digital realm.
Keywords: Metaverse; transatlantic data transfers; EU law; extraterritoriality; data protection shield; data protection; United States